Theoretical Issues of Training Future Agrarians in Higher Education - Lushchyk, Yuliia (Educational Challenges, 2020)
The article purpose is to introduce important theoretical items of training future agrarians in higher education institutions (HEIs) taking into account the views of modern scientists (Ukrainian and foreign) on professional education and training as well as outlining the priorities of higher agricultural education in Ukraine based on the experience of Great Britain. The methodology is introduced by different methods (analysis, synthesis, observation, description) of the research. There are research results in the paper. The literature on the study subject was analyzed and the theoretical ground of agricultural education and training (namely the definitions of training, vocational education, vocational education and training, professional education, agricultural education, training future agrarians in HEIs), were clarified and generalized. The ideas about the nature of agriculture, its importance in modern society, and approaches to agricultural education were cleared up. It was pointed out that the aim and tasks of training future agrarians were correlated with the needs of sustainable agriculture, labor market and human resource development. The aim of the training of future agrarians in higher education is identified as the formation, development and practical application of a wide range of knowledge and skills which are mastered in different subject areas related to agriculture, taking into account such factors as climate change, sustainability, food safety requirements, etc., oriented the professional and personal development of human resources. The priorities in the field of higher agricultural education in Ukraine according to the current national and international tendencies were detected. Conclusions: there is the interrelation between the agriculture and professional education and training in HEIs; clarifying the principle terminology provides an important theoretical precondition for future agrarians training in HEIs; the outlined priorities of higher agricultural education in Ukraine focus on economic, social, and individual aspects and take into account national and international achievements.